Bandgap Tunable Two-Step Vapor-Deposited Perovskite Absorbers for Perovskite-Silicon Tandem Solar Cells - Kuba, Austin G.; Artuk, Kerem; Othman, Mostafa; Turkay, Deniz; Ongaro, Chiara; Debastiani, Michele; Guesnay, Quentin; Golobostanfard, Mohammad Reza; Heydarian, Maryamsadat; Fischer, Oliver; Schubert, Martin C.; Sahli, Florent; et al. (American Chemical Society (ACS), 2026)
We report a two-step thermal evaporation–close space sublimation deposition method for tunable bandgap lead halide perovskites with single junction solar cell efficiencies exceeding 20%. These absorbers are integrated into perovskite–silicon tandem solar cells with stabilized efficiencies of >29%.